Thermal and mechanical properties of bio-cemented quartz sand mixed with steel slag - Shuang Li; Ming Huang; Mingjuan Cui; Kai Xu; Guixiao Jin (Biogeotechnics)
The aim of this study is to disclose the feasibility of improving the thermal conductivity and mechanical strength of quartz sand steel slag mixtures treated by enzyme-induced carbonate precipitation (EICP). In this work, the effects of steel slag content (SSC) and number of treatment cycle (N) on the thermal conductivity and mechanical strength of EICP-treated specimens were investigated. The immersion method was adopted for specimen preparation. The thermal conductivity was measured by transient plane source method (TPS) and the unconfined compressive strength (UCS) was obtained through a uniaxial compression test. Moreover, the SEM test was conducted to obtain the morphology and deposition characteristics of calcium carbonate crystals. The result shows that the thermal conductivity and UCS of EICP-treated sands increase before decreasing as the SSC increases. Consequently, the maximum values of thermal conductivity and UCS are 1.28 W/(m⊡K) and 6.31 MPa, respectively, corresponding to the optimal parameter of 20% SSC at 12 N. The optimal thermal conductivity and UCS increase by 367% and 137%, respectively, compared to that of EICP-treated sand with no addition of steel slag. The SEM analysis indicates that the spherical calcium carbonate exists in the range of 0–20% SSC, whereas there is mainly amorphous calcium carbonate when the SSC varies from 40% to 80%. It also demonstrates that the UCS is more sensitive to the variation of calcium carbonate content than that of thermal conductivity.